2007
DOI: 10.1002/mrd.20825
|View full text |Cite
|
Sign up to set email alerts
|

Live rats resulting from injection of oocytes with spermatozoa freeze‐dried and stored for one year

Abstract: This study was designed to examine whether rat spermatozoa after freeze-drying and 1-year storage can participate in full-term development following intracytoplasmic sperm injection (ICSI). Cauda epididymal spermatozoa from Crlj:Wistar rats were frozen in liquid nitrogen (LN 2 ), first dried for 14 hr at 0.37 hPa and then for 3 hr at 0.001 hPa. The dried spermatozoa were stored for 1 year in a desiccator at þ258C, or in a refrigerator at þ48C, or in LN 2 at À1968C. Controls consisted of sperm that had only bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 20 publications
(35 reference statements)
0
49
0
Order By: Relevance
“…A prolonged storage of FD spermatozoa at ambient temperatures may induce such alterations and/or DNA damage. We have previously reported that one-year storage of FD rat spermatozoa at a room temperature has resulted in a higher incidence of chromosomal aberrations compared to those stored in LN 2 or refrigerator [7]. This has been accompanied with great reduction of cleavage rate after injection of FD sperm stored at +25 ْ◌C (1%) compared to 36-38% after injection of FD sperm stored at +4 or -196 ْ◌C.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…A prolonged storage of FD spermatozoa at ambient temperatures may induce such alterations and/or DNA damage. We have previously reported that one-year storage of FD rat spermatozoa at a room temperature has resulted in a higher incidence of chromosomal aberrations compared to those stored in LN 2 or refrigerator [7]. This has been accompanied with great reduction of cleavage rate after injection of FD sperm stored at +25 ْ◌C (1%) compared to 36-38% after injection of FD sperm stored at +4 or -196 ْ◌C.…”
Section: Discussionmentioning
confidence: 97%
“…Intracytoplasmic injection of freeze-dried spermatozoa has been resulted in successful production of live offspring in mouse [1,[4][5][6]32], rat [3,7,33] and rabbit [2], and blastocyst-stage embryos in cattle [8,9] and pig [10]. However, long-term storage of FD spermatozoa at room temperature has not yet been achieved in any mammalian species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As one of the cryopreservation methods in mammalian spermatozoa, freeze-drying has been applied in mouse [1][2][3][4][5][6][7][8], rat [9,10], rabbit [11], bull [12], boar [13,14] and human [15] spermatozoa. An advantage in freeze-drying is to store the spermatozoa without the use of liquid nitrogen for a long period.…”
Section: Introductionmentioning
confidence: 99%